A SIMPLE HISTOCHEMICAL REACTION FOR ALDEHYDES - ARZAC, JP (Laboratorios Hormona S A, CD MEXICO, DF, MEX, 1978)
Discovery of an impression adds a 3d locality to those from which this sp, and the associated ammonites Inoceramus labiatus and Inoceramus sp have been recorded in n Mexico These 3 may prove reliable indicators of Turonian deposits
J NAT CANCER INST
Keywords: HISTOCHEMICAL, REACTION, ALDEHYDES; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PATOLOGIA CLINICA